Rare popliteal mass following retrograde nailing of ballistic femur fracture: a case report. Issue 1 (11th March 2021) - Court, Tannor; Gusho, Charles A.; Graf, Alexander; Schmeling, Gregory
Abstract: Introduction: Civilian ballistic injuries are commonly associated with fracture, vascular injury, and soft tissue trauma. Posttraumatic pseudoaneurysms represent an extremely rare subset of vascular injuries following ballistic fractures. Case: We present the rare case of a posttraumatic pseudoaneurysm that occurred after retrograde femoral nailing of a ballistic distal femur fracture. The patient presented in clinic postoperatively with a pulsatile popliteal mass. Distal pulses were intact but subsequent ultrasound and angiography revealed a pseudoaneurysm of the distal superficial femoral artery. The pseudoaneurysm was subsequently treated with a covered stent and the patient's recovery was uncomplicated. Conclusion: Due to the potential life and limb-threating complications from pseudoaneurysm rupture, this case report emphasizes the early recognition and expeditious management of vascular complications following ballistic fractures in the civilian population.